MANAJEMEN PENINGKATAN MUTU PESERTA DIDIK - Juliansari, Wilda; Tobari, Tobari; Houtman, Houtman (Graduate Program Magister Manajemen Pendidikan, 2020)
This study aimed at determining the management for improring the quality of Student in SMK PGRI Tanjung Raja. This research is qualitative case study was done by the data triangulation observations, interviews and documentation. The informant as a data source that use in this research is the reseach of internal, 1) the Principal; 2) five head teachers of vocational programs; 3) Students; 4) assistant principal of students affair while external data sources 1) Parents of students; 2) The community is closely related to the management of improving the quality of students in SMK PGRI Tanjung Raja, Ogan Ilir Regency. The results of the study showed that students in SMK PGRI Tanjung Raja first took the test because in SMK had to choose the vocational training to grow their knowledge competencies, and their students' competency skills based on their interests, talents or abilities in vocational expertise. The strategy of principal’s for implementing the improvement of the quality of students is to establish a standardization of management to improve the quality of students in five programs. To improve quality, it demands continuous improvement and can also improve achievement in each department. The way to maintain academic and non-academic achievements can be done by studying and practicing hard. One process of improving the quality of education can be done with school accreditation, namely B (Good) with a value of 86.